Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

For $n\in \mathbb{N}$ and $z\in \mathbb{C}$:

  1. $\sin{(nz)}=\sum _{ k=0 }^{ n }{ \binom{n}{k} }\frac{1}{2i}(i^k-(-i)^k)(\cos{z})^{n-k}(\sin{z})^k $
  2. $\cos{(nz)}=\sum _{ k=0 }^{ n }{ \binom{n}{k} }\frac{1}{2}(i^k+(-i)^k)(\cos{z})^{n-k}(\sin{z})^k $

Formula: $\forall_{z,w\in \mathbb{C}} \ \sin{(z+w)}=\sin{z}\cos{w}+\cos{z}\sin{w}$

Hear is the solution:

Basis for $n=0$

  • $\sin(0)=0=\frac{1}{2i}(i^0+(-i)^0)(\cos{z})^0(\sin{z})^0$
  • $\cos(0)=1)\frac{1}{2}(i^0+(-i)^0)(\cos{z})^0(\sin{z})^0$

Induction hypothesis:

Inductive step: $n \rightarrow n+1$

$\sin{((n+1)z)}=\sin{(nz+z)}=\sin{(nz)}\cos{(z)}+\cos{(nz)}\sin{(z)}= \\ =(\sum_{k=0}^{n}\binom{n}{k}\frac{1}{2i}(i^k-(-i)^k)(\cos{(z)})^{n-k}(\sin{(z)})^k)(\cos{(z)}) \\ +(\sum_{k=0}^{n}\binom{n}{k}\frac{1}{2i}(i^k+(-i)^k)(\cos{z})^{n-k}(\sin{z})^k)(\sin{z})= \\ =\sum_{k=0}^{n}\frac{1}{2i}(i^k-(-i)^k)(\cos{z})^{n+1-k}(\sin{z})^k + \\ +\sum_{k=1}^{n+1}\binom{n}{k-1}\frac{1}{2}(i^{k-1}+(-i)^{k-1})(\cos{z})^{n-(k-1)}(\sin{z})^k= \\ =\binom{1}{0}\frac{1}{2i}(i^0-(-i)^0)(\cos{z})^{n+1}(\sin{z})^0 + \\ + \sum_{k=1}^{n}[\binom{n}{k}+\binom{n}{k-1}]\frac{1}{2i}(i^k-(-i)^k)(\cos{z})^{n+1-k}(\sin{z})^k + \\ + \binom{n}{n}\frac{1}{2i}(i^{n+1}-(-i)^{n+1})(\cos{z})^0(\sin{z})^{n+1}= \\ =\sum_{k=0}^{n+1}\binom{n+1}{k}\frac{1}{2i}(i^k-(-i)^k)(\cos{z})^{n+1-k}(\sin{z})^k$

share|improve this question

2 Answers 2

up vote 1 down vote accepted

Hear is the solution:

Basis for $n=0$

  • $\sin(0)=0=\frac{1}{2i}(i^0+(-i)^0)(\cos{z})^0(\sin{z})^0$
  • $\cos(0)=1)\frac{1}{2}(i^0+(-i)^0)(\cos{z})^0(\sin{z})^0$

Induction hypothesis:

Inductive step: $n \rightarrow n+1$

$\sin{((n+1)z)}=\sin{(nz+z)}=\sin{(nz)}\cos{(z)}+\cos{(nz)}\sin{(z)}= \\ =(\sum_{k=0}^{n}\binom{n}{k}\frac{1}{2i}(i^k-(-i)^k)(\cos{(z)})^{n-k}(\sin{(z)})^k)(\cos{(z)}) \\ +(\sum_{k=0}^{n}\binom{n}{k}\frac{1}{2i}(i^k+(-i)^k)(\cos{z})^{n-k}(\sin{z})^k)(\sin{z})= \\ =\sum_{k=0}^{n}\frac{1}{2i}(i^k-(-i)^k)(\cos{z})^{n+1-k}(\sin{z})^k + \\ +\sum_{k=1}^{n+1}\binom{n}{k-1}\frac{1}{2}(i^{k-1}+(-i)^{k-1})(\cos{z})^{n-(k-1)}(\sin{z})^k= \\ =\binom{1}{0}\frac{1}{2i}(i^0-(-i)^0)(\cos{z})^{n+1}(\sin{z})^0 + \\ + \sum_{k=1}^{n}[\binom{n}{k}+\binom{n}{k-1}]\frac{1}{2i}(i^k-(-i)^k)(\cos{z})^{n+1-k}(\sin{z})^k + \\ + \binom{n}{n}\frac{1}{2i}(i^{n+1}-(-i)^{n+1})(\cos{z})^0(\sin{z})^{n+1}= \\ =\sum_{k=0}^{n+1}\binom{n+1}{k}\frac{1}{2i}(i^k-(-i)^k)(\cos{z})^{n+1-k}(\sin{z})^k$

share|improve this answer

This is just my attempt on this problem...

Can we try to split this sum:

$\sin{(nz+z)}=\sum _{ k=0 }^{ n+1 }{ \binom{n+1}{k} }\frac{1}{2i}(i^k+(-i)^k)(\cos{z})^{(n+1)-k}(\sin{z})^k$

into a sum going from 0 to 1, and another sum going from 0 to n ? Then we can use the inductive hypothesis and the base case, to say that the sum, up to n+1 steps, holds.

After some attempts, everything works until I'm getting stuck at trying to split the combination term. I forgot on how to do it >_<

share|improve this answer
    
You mean to split it in $0\rightarrow n$ and + $n+1$ ,right? –  Devid Feb 3 '13 at 19:29
    
Yes, a sum up to n terms, and isolate the n+1 term out. –  Cecile Feb 3 '13 at 20:36
    
Ok so you mean this: $$\sum_{k=0}^{n}\binom{n}{k}\frac{1}{2i}(i^k-(-i)^k)(\cos{z})^{n-k}(\sin{z})^k+ \binom{n+1}{k}\frac{1}{2i}(i^k-(-i)^k)(\cos{z})^{n+1-k}(\sin{z})^k$$ and now ? –  Devid Feb 3 '13 at 20:44

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.